5 - Capitalism, Globalisation and the Underdevelopment Process in Africa: History in Perpetuity - Olutayo, Akinpelu O.; Omobowale, Ayokunle O. (Africa Development, 2007)
Since the incorporation of the Third World nations into the world capitalist system, the underdevelopment process seems to have commenced through the use of liberal economic principles. In spite of the obvious pauperisation of these nations, it seems as if there is no alternative even when indigenous governments are in control of affairs. This paper attempts to show why the underdevelopment process has persisted with capitalism entrenched in the garb of globalisation. It suggests that the way out is for the developing world to control and own their means of survival without which the underdevelopment process shall continue. Of utmost significance however is the need to control the intellectual domain.